2021
DOI: 10.1515/ijmr-2020-7998
|View full text |Cite
|
Sign up to set email alerts
|

Development of an accelerated test for pitting corrosion of CUSTOM 450 by rDHM

Abstract: A key application of CUSTOM 450 alloy is in the construction of gas turbine compressor blades. The study of pitting corrosion can prevent the failure of many gas turbine compressor blades. In this study, a reflective digital holography microscopy method was employed to investigate the growth of pitting corrosion in depth. To this end, a constant potential of 350 mVSCE in a 3.5 wt.% NaCl solution was applied to the specimen. The generated pits were simulated in three dimensions, and it was indicated that pittin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…According to figure 10 and table 6, it can be seen that there is a tendency to pitting in all specimens since E rp is more negative than E pit for them [75,83]. Meanwhile, positive hysteresis (reverse scan current density is greater than that for the forward scan) is observed in the curves of the specimens, which can be a sign of the susceptibility to pitting corrosion and initiation of pits in the transpassive region [78,80].…”
Section: Potentiodynamic Polarization Testmentioning
confidence: 87%
“…According to figure 10 and table 6, it can be seen that there is a tendency to pitting in all specimens since E rp is more negative than E pit for them [75,83]. Meanwhile, positive hysteresis (reverse scan current density is greater than that for the forward scan) is observed in the curves of the specimens, which can be a sign of the susceptibility to pitting corrosion and initiation of pits in the transpassive region [78,80].…”
Section: Potentiodynamic Polarization Testmentioning
confidence: 87%
“…More recent developments with multiscale characterization techniques that assess surface topography changes at the nanoscale have enabled the electrochemical determination of dissolution rates. Particularly, the atomic force microscopy (AFM) [18][19][20][21][22][23][24] and quantitative phase microscopy (QPM) techniques, including vertical scanning interferometry (VSI) [25][26][27][28] and digital holographic microscopy (DHM), [29][30][31][32][33][34][35][36][37][38] have evolved as major microto nanoscale topographic techniques to provide early-stage visualization and quantification of corrosion at the nanoscale. The powerful approach provides different types of information (e.g., characteristics of grains, phases, and surface layers) and insights into the region of interest to gain a comprehensive understanding of the corroding system.…”
mentioning
confidence: 99%
“…Journal of The Electrochemical Society, 2022 169 111502 corroded grain boundaries distinguished between IGC and TGC and found that the stainless steel predominantly suffered from IGC corrosion. Pedram et al 31 also developed an accelerated test for pitting corrosion by rDHM and compare it in the actual working condition. From DHM surface topography results, pitting corrosion was observed at 350 mV SCE applied potential, with the pits growing rapidly (250 μm) in the first 10 min while growing just 50 μm in depth at the last 10-min interval.…”
mentioning
confidence: 99%